Kesan penuaan sesuhu terhadap sifat mikro kekerasan pempaterian Sn-Ag-Cu/cnt/cu menggunakan pelekukan nano (Effect of isothermal aging on microhardness properties of Sn-Ag-Cu/CNT/Cu using nanoindentation) - Ismail, Norliza; Jalar, Azman; Abu Bakar, Maria; Ismail, Roslina; Safee, Nur Shafiqa; Ismail, Ahmad Ghadafi; Ibrahim, Najib Saedi (Penerbit Universiti Kebangsaan Malaysia, 2019)
Effect of thermal aging towards hardness properties of Sn-3.0Ag-0.5Cu (SAC305) solder joint added with carbon nanotube (CNT) particles was investigated. Hardness properties indicate the strength of solder was determined by nanoindentation approach. SAC solder alloy was added with 0.03% weight percent of CNT to form SAC305-CNT solder paste. Printed solder paste on printed circuit board (PCB) with copper (Cu) surface finish underwent reflow soldering at peak temperature 260°C to form SAC305 and SAC305-CNT solder joint. Then, SAC305 and SAC305-CNT were exposed to thermal aging via high temperature storage test (HTS) at constant temperature 150°C for about 200, 400, 600, 800 and 1000 h. Solder joint samples after reflow and thermal aging were analysed using nanoindentation method to determine hardness properties. For microstructure analysis, samples were etched and images were captured via optical microscope. The results showed microhardness values decrease with increasing of aging time for both investigated solder joints. However, hardness values for SAC305-CNT solder joint was higher (~10-26%) compared to SAC305 solder joint without CNT. From nanoindentation test, localized microhardness properties of solder joint under isothermal aging have been attained. Trend of microhardness values obtained was parallel with the trend gained by using conventional hardness test. © 2019 Penerbit Universiti Kebangsaan Malaysia. All rights reserved.